2007
DOI: 10.1007/s10815-006-9081-x
|View full text |Cite
|
Sign up to set email alerts
|

Light exposure of the ovum and preimplantation embryo during ART procedures

Abstract: Exposure to visible light (400-700 nm wavelengths) is an unnatural stress factor to preimplantation embryos cultured in vitro. This study investigated the spectral composition and intensity of light during IVF procedures, and calculated radiation doses reaching the embryo during handling and manipulation. The study shows that normal IVF procedure may result in stressing radiation doses, unless filters are applied. This is at present not sufficiently recognised. No Danish IVF clinics use filters to protect embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 14 publications
1
75
0
Order By: Relevance
“…a typical time frame of 30 min for performing an intracytoplasmic sperm injection on the inverted microscope. It is thus important to reduce the light exposure during such in-vitro manipulations, either by decreasing exposure time and irradiance [15,27] or by avoiding harmful wavelengths by the use of filters or LED's with a more narrow spectral emission [2,28].…”
Section: Discussionmentioning
confidence: 99%
“…a typical time frame of 30 min for performing an intracytoplasmic sperm injection on the inverted microscope. It is thus important to reduce the light exposure during such in-vitro manipulations, either by decreasing exposure time and irradiance [15,27] or by avoiding harmful wavelengths by the use of filters or LED's with a more narrow spectral emission [2,28].…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit, whose oocytes and zygotes withstand strong light, could be an opposite extreme. Even though humans may be close to the rabbit in this respect (17), exposure of oocytes, zygotes, and *Zygotes were exposed to cool white fluorescent light (1,200 lx, 15 min) and then cultured in the dark until they reached the blastocyst stage. Zygotes handled in the same manner but shielded from light by wrapping the dishes with aluminum foil served as controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that extensive light exposure may be detrimental to embryo development, and especially that short wavelength light exposure should be minimized [4,27,28,40]. Furthermore, heat due to motion and friction of moving parts; presence of magnetic fields, sheer stress of moving culture dishes and presence of lubricants may each represent theoretical risks to embryo development.…”
Section: Introductionmentioning
confidence: 99%